2001
DOI: 10.1176/appi.ajp.158.8.1227
|View full text |Cite
|
Sign up to set email alerts
|

CSF Norepinephrine Concentrations in Posttraumatic Stress Disorder

Abstract: These findings reveal the presence of greater CNS noradrenergic activity under baseline conditions in patients with chronic PTSD than in healthy subjects and directly link this pathophysiologic observation with the severity of the clinical posttraumatic stress syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
261
2
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 413 publications
(275 citation statements)
references
References 31 publications
6
261
2
6
Order By: Relevance
“…In this regard, NPY has a reciprocal functional relationship with both norepinephrine (15) and corticotropin-releasing hormone (CRH) (16). Interestingly, our previous data showing elevated basal CRH and norepinephrine concentrations in the CSF of combat-related PTSD patients (17,18) are consistent with the current finding.…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, NPY has a reciprocal functional relationship with both norepinephrine (15) and corticotropin-releasing hormone (CRH) (16). Interestingly, our previous data showing elevated basal CRH and norepinephrine concentrations in the CSF of combat-related PTSD patients (17,18) are consistent with the current finding.…”
Section: Discussionsupporting
confidence: 92%
“…Elevated NE and metabolites have been found in the cerebrospinal fluid, plasma, or brain tissue of schizophrenia patients (Yamamoto and Hornykiewicz, 2004), the cerebrospinal fluid of Tourette's (Leckman et al, 1995) and PTSD patients (Geracioti et al, 2001), and abnormalities in the LC itself also have been reported in schizophrenia patients (Gay et al, 1989;Lohr and Jeste, 1988;Marner et al, 2005). Because the present findings indicate that pharmacological stimulation of the LC-NE pathway is sufficient to disrupt PPI and dysregulation of the LC-NE system has been implicated in all of these conditions (Boehnlein and Kinzie, 2007;Robbins and Arnsten, 2009;Yamamoto and Hornykiewicz, 2004), it may be that altered tonic LC activity is a mechanism for the deficient sensorimotor gating that is seen in a subset of patients, regardless of their nosological classification into various illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…The reconsolidation process is particularly relevant for PTSD, in which persistent and recurring recall of the traumatic event may strengthen the traumatic memory over time, while also providing an opportunity for recall-based pharmacological intervention. Indeed, evidence from studies of rodents indicates that enhanced noradrenergic signaling, such as that observed in PTSD patients (Geracioti et al, 2001), is associated with enhancement of fear memory during reconsolidation and a subsequent increase in resistance to fear extinction (Debiec et al, 2011).…”
Section: Memory Erasurementioning
confidence: 99%